In memoriam Apáczai Kiadó (Training and Practice : Journal of Educational Sciences, 2015)
Education policy is subject to changes from time to time that may divert the knowledge of teachers and instructors towards other directions. After the changing of the system in Hungary more and more textbook publishers appeared, one of them was the Apáczai Publisher. In my opinion it supported education in such a complex way that it could perfectly serve the growing generations and their pedagogues according to the relevant education system. As a result the publisher provided the continuous innovative improvement of the person and the institution that was aimed at. In my study I would like to show a comprehensive view of the Publisher’s activity based on facts. Among the Hungarian publishers this was the only one that was working as a Hungarian private company until May 2014. However the first school year has passed ’without Apáczai Publisher’ and the market of school-books has changed radically its textbook writers and collegaues are still present and play an important role in  the work of the Education Authority.